FACTORS RELATED TO THE UTILIZATION OF HEALTH SERVICES AT TRADITIONAL COMMUNITY HEALTH CENTER IN MAKASSAR - Eka Ernalifia Saputri; Razak, Amran; Abadi, Muh. Yusri (Universitas Islam Negeri Alauddin Makassar, 2023)
Background: Treatment methods through traditional healers and using herbal ingredients are an alternative for the community in overcoming health problems experienced, in addition to using conventional health services. Objective: This study aims to determine the factors related to the use of health services at Traditional Community Health Center in Makassar (Balai Kesehatan Tradisional Masyarakat Makassar/BKTM) in 2023. Methods: This research was conducted at Traditional Community Health Center in Makassar in May 2023. The population of this study were all outpatients in all types of services. The sample size was 95 respondents. The research method employed was a cross-sectional design with a quantitative approach. The data analysis techniques used were univariate and bivariate, and the tests applied was chi-square test. Results: The study's findings revealed that the utilization of health services at Traditional Community Health Center in Makassar was associated with three factors: availability(p=0.048), affordability(p=0.000) and accessibility(p=0.085). Conclusion: The utilization of health services at Traditional Community Health Center in Makassar correlated with availability, affordability, and accessibility. It is recommended for the management to improve facilities that are not yet available, as well as increase promotion and publication regarding traditional health services and the existence of the Balai Kesehatan Traditional Masyarakat Makassar.